Shared social responsibility. Dual role of consumers as stakeholders in firm strategy. Issue 1 (5th December 2019) - Barboza, Gustavo; Pede, Valerien; Madero, Sergio
Abstract : Purpose: The purpose of this paper is to model the role that stakeholders, and especially social responsible consumers play in the process of finding a win–win solution to control production related negative externalities. In this regard, when information asymmetries are present and consumers become knowledgeable about them, consumers with d-preferences for corporate social responsibility (CSR) type of products becomes the driver of the firm strategy. Design/methodology/approach: To accomplish the goals of this paper, the authors proceed to develop a series of theoretical models wherein the social gains and costs of alternative modes of intervention are illustrated. The authors begin with a standard Pigouvian tax model and construct a stakeholder equivalent tax model and finalize the analysis with consumers acting in a shared social responsible behavior with firms as the optimal solution model. Findings: The authors show that proactive disclosure of information asymmetries regarding negative externalities develops a shared social responsibility between consumers and firms. Market-based solutions to the externality problem are achieved under this setting. This solution is preferred to a Pigouvian tax and to a stakeholder equivalent tax. It is concluded that shared social responsibility is the result of the interaction of consumers with d-preferences and the reaction of a socially responsible "firm" willing, and the authors are able to incorporate these preferences as drivers for its strategy. Research limitations/implications: The main limitation of this paper is in its theoretical nature and specific applications to one case, that of negative externalities in production processes. The implication of this is that the model herein developed needs to be put to the empirical test. Social implications: The overall social implications indicate that active reduction of information asymmetries is welfare improving and preferred to government intervention. Originality/value: This paper is original as it makes use of economic principles to develop a parsimonious model to demonstrate that proactive actions of a firm in response to consumers and stakeholders demands leads to an overall social welfare improvement when negative externalities deriving from production are incorporated into the decision making process of both consumers and firms. These decisions prove superior to government regulations.